PERTUMBUHAN GULMA ALANG-ALANG (Imperata cylindrica L. Beauv.) PADA BERBAGAI KONDISI KEPADATAN SETELAH PEMOTONGAN DI PETROCHINA INTERNATIONAL JABUNG LTD. - Yuni Ratna; Elly Indra Swari; Alan Firmansyah (Universitas Batanghari, 2022)
This research aims to find out the growth of I. cylindricaweed after cutting at various density conditions so that it can be determined the interval of precise control mechanically in the pipeline PetroChina International Jabung Ltd. The research was conducted by making random sample plots in various conditions of I. cylindrica population density. There were three population densities of I. cylindricaobserved, namely dense,mediun and rare. The results showed that height, number of tillers and dry weight of I. cylindrica were higher in dense and medium population densities than rare population densities. There is a shift in the dominant weed species in each condition of population density after cutting. The community of vegetation before and after cuttingat dense population density was classified as homogeneous with C value of 78.05%, while at medium and rare population density it wasclassifiedas heterogeneous with C value of < 75%.Keywords:Imperata cylindrica, growth of weed, population density, species shift